IMPLEMENTASI MODEL EOQ PADA PEMBANGUNAN SISTEM PENUNJANG KEPUTUSAN PENGENDALIAN PERSEDIAAN BAHAN BAKU DI PERCETAKAN MAJESTY MALANG - Wahyuningsih, Dian (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
A company with production activity would require raw materials. The raw materials are processed into useful products to satisfy consumer needs and market. Inventory control of raw materials into a very complex problem due to inventory control of raw materials that will either launch the entire production. Problems that can occur in the absence of raw material inventory control is the inhibition of the production process and the more fatal is the dismissal of the endless activities for feedstock production.Calculation of raw materials can be performed using EOQ model, model calculations are simple but effective enough to be able to provide an alternative to the purchasing decision to order the appropriate materials, so as to avoid the worst possibilities regarding feedstock. This study aims to provide an alternative to a decision on the purchase order the purchase of raw materials that can predict the exact needs of the raw for the next period. Keywords: EOQ Model, Decision Support System, Inventory Control